HUBUNGAN POSISI APOKOL DALAM PERKECAMBAHAN AREN (Arenga pinnata Merr.) DENGAN PERTUMBUHAN KECAMBAH DAN KERAGAMAN GENETIK - Anwar, Aswaldi; Dwipa, Indra; Hervani, Dini; Sari, Afrima (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Sugar palm seed germination does indicate by the appearance of a tissue that extends like a sponge called apokol which is penetrating the hard seed coat and can occur in several positions in germinated sugar palm seeds. No research reports discuss the relationship between this apokol position and the phenology of sugar palm seed germination. This research aims to study the relationship between apokol position and the growth of sugar palm seedlings and their genetic diversity. The research applies Experiment in Completely Random Design with four treatments, each repeated five times. The four treatments are the apokol position, namely A: Apokol in right-center, B: Apokol in left-center, C: Apokol in left-bottom, and D: Apokol in right-bottom. The results showed that the fastest time for the coleoptile emergence was 40 days after transplanting in the right-center apokol position. Morphologically, there was no significant difference in the sugar palm seedling growth with each apokol position. On the other hand, we found that there were genetic diversities among them revealed by Simple Sequence Repeat (SSR) markers. The palm seeds with the right-center apokol position included the first cluster, and the second cluster consisted of left-center apokol, right- bottom apokol, and left-bottom apokol.